Syn-eruptive hydrothermal degassing and CO2 fluxes at the Planchón-Peteroa Volcanic complex (Chile-Argentina): evidence from dissolved gases, isotopes, and radon tracers - L. Ruggiero; A. Sciarra; N. Vigide; M.C. Tartarello; H. Barcelona; R. Maffucci; A. Conti; G. Galli; S. Bigi (Journal of Volcanology and Geothermal Research, 2026)

Unveiling “Mid-Pliocene Warm Period” dynamics through multiproxy stratigraphic analysis: The Valdelsa Basin in Northern Apennines – Italy as a key archive - L. Milaneschi; G. Cornamusini; P. Conti; I. Martini; J. Maffei; F. Cifelli; M. Mattei; S. Da Prato; M.C. Alçiçek; L.M. Foresi (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Interpretable deep learning reveals spatiotemporal MRI features of brain aging that align with neurodegeneration - Nikhil N. Chaudhari; Owen M. Vega; Phoebe Imms; Jaron M. Kawamura; Nahian F. Chowdhury; Tamara Jafar; Andrei Irimia; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; et al. (GeroScience, 2026)
Cortical thinning and atrophy are hallmarks of brain aging that have been characterized using magnetic resonance imaging (MRI). Brain aging involves many neuroanatomic features whose effects on brain structure remain unexplored. To address this challenge, we trained interpretable deep neural networks (DNNs) to estimate brain age (BA) from T 1 -weighted ( T 1 w) MRI. By identifying MRI features unapparent to humans, DNNs can find aging-related structural alterations above and beyond cortical thickness and atrophy. Using a novel approach to DNN interpretability, we mapped brain aging progression in 25,539 cognitively normal UK Biobank adults aged 45–83 years. Cortical aging is found to involve anatomic features becoming prominent during the 50s within frontolateral, mesolimbic, cuneal, and occipitotemporal regions. From these foci, aging-related features propagate to adjacent areas at rates peaking in the 60s. Cortical thinning and atrophy do not trend closely with neurodegeneration, but important DNN-identifiable anatomic features have spatiotemporal dynamics that match those of amyloid or tau. Our results challenge the assumption that MRI cannot map anatomic features trending with neurodegeneration. Interpretable DNNs can empower MRI to quantify anatomic aging as a process of spatial feature expansion from focal regions into nearby structures in the sequence of neurodegenerative pathology. Traditional morphometrics explain only ∼1% of variance in DNN-identifiable features, which clarifies why the former are insensitive to anatomic changes involving neurodegeneration. Our results conceptualize brain aging in the context of spatial and temporal parallels between anatomic senescence and neuropathology. These findings may help to map cognitively normal adults’ neurodegenerative anatomy even without PET measurements. Graphical Abstract

Sex and APOE genotype specific brain regional vulnerability to Alzheimer's Disease - Qi Zeng; Minghui Wang; Erming Wang; Xianxiao Zhou; Peng Xu; Vahram Haroutunian; Dongming Cai; Bin Zhang; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; et al. (GeroScience, 2026)
Alzheimer’s disease (AD) disproportionately affects women and carriers of the apolipoprotein E ε4 allele (APOE4), yet little is known about how sex and APOE interact to influence white matter (WM) integrity during disease progression. We integrated diffusion MRI and matched blood transcriptomic data to investigate these interactions and their underlying biological mechanisms. WM microstructure was quantified using diffusion tensor imaging (DTI) and neurite orientation dispersion and density imaging (NODDI), and regional vulnerability was assessed with a composite vulnerability score (CVS) derived from associations between diffusion features and AD severity across clinical traits in each of the four sex-APOE groups (female or male, with or without APOE4). Brain parcellation with the Eve atlas revealed regions consistently affected across sex-APOE groups (e.g., parahippocampal and superior temporal gyri) and regions specific to individual groups (e.g., the cingulum in females with APOE4 and the middle frontal gyrus in males without APOE4). Gene co-expression network analysis of the matched blood expression data identified gene subnetworks linked to group-specific regional vulnerability, including a muscle tissue morphogenesis module regulated by NEURL1B and HIST1H2BN associated with middle frontal gyrus vulnerability. These findings demonstrate that sex and APOE genotype jointly shape region-specific WM vulnerability and its molecular signatures in AD. Understanding these interactions provides novel mechanistic insights and may inform precision approaches to drug development, biomarker discovery, and clinical trial design for AD.

Biopsychosocial frailty and the incident risk of cardio- and cerebrovascular diseases: an 8-year follow-up of the italian longitudinal study on aging - Vincenzo Solfrizzi; Emanuele Scafato; Madia Lozupone; Carlo Custodero; Vittorio Dibello; Donato Cirrottola; Claudio Pace; Marika Rizzato; Andrea Schilardi; Claudia Gandin; Silvia Ghirini; Rodolfo Sardone; et al. (GeroScience, 2026)

The daily rhythms of temperature preference are conserved in nocturnal and blind fish - F. Conti; E. Gatto; G. de Alba; S. Pintos; J.F. López-Olmeda; L.M. Vera; S. Rey Planellas; S.A. Mackenzie; C. Bertolucci; F.J. Sánchez-Vázquez (Journal of Thermal Biology, 2025)

Immunization of rabbits with nanovenom composed of Dendroaspis polylepis venom and silica nanoparticles: a first in vivo approach - Federico G. Baudou; María Herrera; Mariángela Vargas; Mauren Villalta; Florencia S. Conti; Exequiel Giorgi; Laura Leiva; José María Gutiérrez; Adolfo R. de Roodt; Mauricio de Marzi (Toxicon, 2025)

Predicting the progression of MCI and Alzheimer’s disease on structural brain integrity and other features with machine learning - Marthe Mieling; Mushfa Yousuf; Nico Bunzeck; Michael Weiner; Paul Aisen; Ronald Petersen; Clifford R. Jack; William Jagust; Susan Landau; Monica Rivera-Mindt; Leslie M. Shaw; Edward B. Lee; et al. (GeroScience, 2025)
Machine learning (ML) on structural MRI data shows high potential for classifying Alzheimer’s disease (AD) progression, but the specific contribution of brain regions, demographics, and proteinopathy remains unclear. Using Alzheimer’s Disease Neuroimaging Initiative (ADNI) data, we applied an extreme gradient-boosting algorithm and SHAP (SHapley Additive exPlanations) values to classify cognitively normal (CN) older adults, those with mild cognitive impairment (MCI) and AD dementia patients. Features included structural MRI, CSF status, demographics, and genetic data. Analyses comprised one cross-sectional multi-class classification (CN vs. MCI vs. AD dementia, n = 568) and two longitudinal binary-class classifications (CN-to-MCI converters vs. CN stable, n = 92; MCI-to-AD converters vs. MCI stable, n = 378). All classifications achieved 70–77% accuracy and 61–83% precision. Key features were CSF status, hippocampal volume, entorhinal thickness, and amygdala volume, with a clear dissociation: hippocampal properties contributed to the conversion to MCI, while the entorhinal cortex characterized the conversion to AD dementia. The findings highlight explainable, trajectory-specific insights into AD progression.

Natural-based solutions to mitigate dietary microplastics side effects in fish - N. Cattaneo; M. Zarantoniello; F. Conti; A. Tavano; A. Frontini; I. Sener; G. Cardinaletti; I. Olivotto (Chemosphere, 2024)

Effect of different deficit irrigation regimes on vine performance, grape composition and wine quality of the “Primitivo” variety under mediterranean conditions - P. Losciale; L. Conti; S. Seripierri; V. Alba; F. Mazzone; L. Rustioni; G. di Leo; F. Tarricone; L. Tarricone (Irrigation Science, 2024)
Climate change represents one of the current major challenges and the improper use of water resources is an impeding threat. Agricultural research can play a crucial role by developing innovative strategies and techniques to reduce water use without affecting crop productivity and quality, particularly in grapevine growing in Mediterranean areas, as both productivity and wine quality are quintessential for the economic and ecologic sustainability of this crop. The present study aimed to define a deficit irrigation strategy for the “Primitivo” grapevine cultivar, taking into account the overall pathway of the vineyard performance in terms of leaf functionality, starch reserves, vine productivity, and wine quality. The trial was carried out in Southern-Italy on a three year-old, drip irrigated vineyard, imposing four deficit irrigation regimes for two consecutive seasons, consisting of 29 (T29), 55 (T55), 85 (T85) and 100% (T100) of crop evapotranspiration (ET C ). Mild water restriction (T85) did not affect vegetative nor reproductive vine performance. Deficit irrigation at 55% ET C lowered leaf functionality, starch accumulation, vine vigour and yield, due to a reduction of cluster weight; however, wine acidity and phenolic compounds were increased. T29 further decreased yield, as also the number of clusters was reduced. The most water-stressed treatment revealed a low concentration of malic acid in the must and a consequent increase of the ethanol sensation in the wine. After 9 months ageing, T85 had the highest wine colour intensity suggesting this treatment as the most promising in terms of quality and quantity of wine as well as for water saving.

The last cave lion of the late Upper Palaeolithic: The engraved feline of Grotta Romanelli (southern Italy) - D. Sigari; C. Bourdier; C. Conti; J. Conti; L. Forti; M. García-Diez; G. Lai; I. Mazzini; P. Pieruccini; R. Sardella (Quaternary Science Reviews, 2024)

Performance of Hermetia illucens (Diptera: Stratiomyidae) larvae reared on organic waste diets and pupal chitin and chitosan yield - Christina Adamaki-Sotiraki; Linda Abenaim; Alessia Mannucci; Christos I. Rumbos; Stefano Bedini; Antonella Castagna; Giuseppe Conte; Monica Tognocchi; Victor Dolianitis; Christos G. Athanassiou; Barbara Conti (Environmental Science and Pollution Research, 2024)

A second update to the checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; G. Calvia; et al. (Plant Biosystems, 2024)

A second update to the checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; A. Alessandrini; N. M. G. Ardenghi; G. Bacchetta; E. Banfi; G. Barberis; L. Bernardo; D. Bouvet; M. Bovio; M. Castello; et al. (Plant Biosystems, 2024)

Breast density in NF1 women: a retrospective study - R. De Santis; G. Cagnoli; B. Rinaldi; D. Consonni; Beatrice Conti; M. Eoli; A. Liguori; M. Cosentino; G. Carrafiello; O. Garrone; M. Giroda; C. Cesaretti; et al. (Familial Cancer, 2024)
Neurofibromatosis type 1 (NF1) is an autosomal dominant condition caused by neurofibromin haploinsufficiency due to pathogenic variants in the NF1 gene. Tumor predisposition has long been associated with NF1, and an increased breast cancer (BC) incidence and reduced survival have been reported in recent years for women with NF1. As breast density is another known independent risk factor for BC, this study aims to evaluate the variability of breast density in patients with NF1 compared to the general population. Mammograms from 98 NF1 women affected by NF1, and enrolled onto our monocentric BC screening program, were compared with those from 300 healthy subjects to verify differences in breast density. Mammograms were independently reviewed and scored by a radiologist and using a Computer-Aided Detection (CAD) software. The comparison of breast density between NF1 patients and controls was performed through Chi-squared test and with multivariable ordinal logistic models adjusted for age, body mass index (BMI), number of pregnancies, and menopausal status.breast density was influenced by BMI and menopausal status in both NF1 patients and healthy subjects. No difference in breast density was observed between NF1 patients and the healthy female population, even after considering the potential confounding factors.Although NF1 and a highly fibroglandular breast are known risk factors of BC, in this study, NF1 patients were shown to have comparable breast density to healthy subjects. The presence of pathogenic variants in the NF1 gene does not influence the breast density value.

New olive-pomace fertilizer tested with a 2-tiers approach: Biomarkers on Eisenia fetida, physiochemical effects on Solanum lycopersicum and Olea europaea - S. Parri; T. Campani; V. Conti; G. Cai; M. Romi; S. Casini; R. Zari; F. Caldini; L. Marsili (Journal of Environmental Management, 2024)

Synthesising the diversity of European agri-food networks: A meta-study of actors and power-laden interactions - Tim G. Williams; Sibylle Bui; Costanza Conti; Niels Debonne; Christian Levers; Rebecca Swart; Peter H. Verburg (Global Environmental Change, 2023)

Tumor and peritumoral adipose tissue crosstalk: De-differentiated adipocytes influence spread of colon carcinoma cells - G. Conti; L. Calderan; L.A. Quintero Sierra; A. Conti; R. Ossanna; F. Boschi; P. Marzola; F. Ferrarini; M. Governa; P.M.-J. Lievens; A. Sbarbati (Tissue and Cell, 2023)

Juvenile polyposis diagnosed with an integrated histological, immunohistochemical and molecular approach identifying new SMAD4 pathogenic variants - Andrea Mafficini; Lodewijk A. A. Brosens; Maria L. Piredda; Cristian Conti; Paola Mattiolo; Giulia Turri; Maria G. Mastrosimini; Sara Cingarlini; Stefano F. Crinò; Matteo Fassan; Paola Piccoli; Michele Simbolo; et al. (Familial Cancer, 2022)
Juvenile polyposis (JP) is a rare familial syndrome characterized by the development of numerous hamartomatous polyps of the gastrointestinal tract and by an increased risk of developing gastrointestinal cancers. It follows a pattern of autosomal dominant inheritance and is associated with germline variants of SMAD4 or BMPR1A genes. Differential diagnosis may be difficult based on histology alone, due to morphological similarities to other familial syndromes. Here we report a case of familial JP diagnosed in a 50-years woman with a familial history positive for gastrointestinal cancers and other tumor types. The patient presented with severe iron deficiency anemia and showed numerous polyps in the stomach and jejunum according to endoscopy and imaging. She underwent an intra-gastric laparoscopic removal of the major gastric polyp, followed by jejunal exploration and resection of a segment with multiple neoformations. Histological examination revealed the presence of hamartomatous polyposis. Gastric and intestinal samples were analyzed with next-generation sequencing. Molecular analysis showed that the patient harbored a germline splicing site variant of SMAD4 , c.1139 + 3A > G, which was complemented by different somatic variants of the same gene in the different polyps. Immunohistochemistry for SMAD4 confirmed loss of protein expression in the polyps, with regular expression in normal cells. cDNA sequencing further confirmed the findings. We thus definitively diagnosed the woman as having JP thanks to an integrated approach based on histology, immunohistochemistry and molecular analysis. The identified variants, all previously reported as variants of unknown significance, were classified as pathogenic as they complemented each other leading to SMAD4 loss.

Microfabricated cantilevers for parallelized cell-cell adhesion measurements - Michele Zanetti; Suet Nee Chen; Martina Conti; Matthew R. G. Taylor; Orfeo Sbaizero; Luisa Mestroni; Marco Lazzarino (European Biophysics Journal, 2022)

IDPlanT: the Italian database of plant translocation - Thomas Abeli; Martina D’Agostino; Simone Orsenigo; Fabrizio Bartolucci; Rita Accogli; Giulia Albani Rocchetti; Claudia Alessandrelli; Arianna Amadori; Filippo Amato; Claudia Angiolini; Silvia Assini; Gianluigi Bacchetta; et al. (Plant Biosystems, 2021)

Effects of tetracycline on entomopathogenic nematodes and their bacterial symbionts - M. Clausi; D. Leone; A. Strano; A. Lizio; G. Rappazzo; C. Mulder; E. Conti (Ecotoxicology, 2021)

Molecular fossils as a tool for tracking Holocene sea‐level change in the Loch of Stenness, Orkney - Martina L. G. Conti; Martin R. Bates; Richard C. Preece; Kirsty E. H. Penkman; Brendan J. Keely (Journal of Quaternary Science, 2020)
Sediments deposited in the Loch of Stenness (Orkney Islands, Scotland) during the Holocene transgression, previously dated to between ~5939–5612 bp , were analysed for molecular fossils – lipids and chlorophyll pigments from primary producers – that complement conventional microfossil and lithological approaches for studying past sea‐level change. While microfossil and lithological studies identified a transgression between 102 and 81 cm core depth, key molecular fossils fluctuate in occurrence and concentration between 118 and 85 cm, suggesting an earlier start to the transgression. Terrestrial lipid concentrations decreased and algal‐derived, short‐chain, n ‐alkanoic acid concentrations increased at 118 cm, indicating a disruption of the freshwater lake conditions associated with the early stages of the marine transgression. The lipid and pigment analyses provided information that complements and extends that from microfossil analysis, presenting a more complete record of Holocene sea‐level changes and local vegetation changes in the Loch of Stenness. The isostatic stability of Stenness during the Holocene points towards other factors to explain the transgression, such as regional factors and/or melting of the Antarctic ice sheet (which occurred up to 3 ka).

Festuca valesiaca Schleich. ex Gaudin newly discovered in the Central Apennines (Italy): a further example of steppe relict in the Abruzzo “dry valleys” - Goffredo Filibeck; Laura Cancellieri; Fabrizio Bartolucci; Ute Becker; Fabio Conti; Samuele Maestri; Marlene Mürz; Elena Schommer; Marta G. Sperandii; Thomas Becker (Plant Biosystems, 2020)

Bioinformatics design and experimental validation of influenza A virus multi-epitopes that induce neutralizing antibodies - G. Lizbeth Ramírez-Salinas; Jazmín García-Machorro; Saúl Rojas-Hernández; Rafael Campos-Rodríguez; Arturo Contis-Montes de Oca; Miguel Medina Gomez; Rocío Luciano; Mirko Zimic; José Correa-Basurto (Archives of Virology, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Grotta Romanelli (Lecce, Southern Italy) Between Past and Future: New Studies and Perspectives for an Archaeo-geosite Symbol of the Palaeolithic in Europe - R. Sardella; D. A. Iurino; B. Mecozzi; D. Sigari; F. Bona; L. Bellucci; M. Coltorti; J. Conti; G. Lembo; B. Muttillo; I. Mazzini (Geoheritage, 2019)

Grotta Romanelli (Lecce, Southern Italy) Between Past and Future: New Studies and Perspectives for an Archaeo-geosite Symbol of the Palaeolithic in Europe - R. Sardella; D. A. Iurino; B. Mecozzi; D. Sigari; F. Bona; L. Bellucci; M. Coltorti; J. Conti; G. Lembo; B. Muttillo; I. Mazzini (Geoheritage, 2019)

Correction to: Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Developing allometric models to predict the individual aboveground biomass of shrubs worldwide - G. Conti; L. D. Gorné; S. R. Zeballos; M. L. Lipoma; G. Gatica; E. Kowaljow; J. I. Whitworth‐Hulse; A. Cuchietti; M. Poca; S. Pestoni; P. M. Fernandes (Global Ecology and Biogeography, 2019)
Aim Existing global models to predict standing biomass are based on trees characterized by a single principal stem, well developed in height. However, their use in open woodlands and shrublands, characterized by multistemmed species with substantial crown development, generates a high level of uncertainty in biomass estimates. This limitation led us to (a) develop global models of shrub individual aboveground biomass based on simple allometric variables, (b) to compare the fit of these models with existing global biomass models, and (c) to assess whether models fit change when bioclimatic variables are considered. Location Global. Time period Present. Major taxa studied 118 species of shrubs. Methods We compile a database of 3,243 individuals across 49 sites distributed worldwide. Including stem basal diameter, height and crown diameter as predictor variables, we built potential models and compared their fit using generalized least squares. We used mixed effects models to determine if bioclimatic variables improved the accuracy of biomass models. Results Although the most important variable in terms of predictive capacity was stem basal diameter, crown diameter significantly improved the models’ fit, followed by height. Four models were finally chosen, with the best model combining all these variables in the same equation [ R 2 = 0.930, root mean square error (RMSE) = 0.476]. Selected models performed as well as established global biomass models. Including the individual bioform significantly improved the models’ fit. Main conclusions Stem basal diameter, crown diameter and height measures could be combined to provide robust aboveground biomass (AGB) estimates of individual shrub species. Our study supplements well‐established models developed for trees, allowing more accurate biomass estimation of multistemmed woody individuals. We further provide tools for a methodological standardization of individual biomass quantification in these species. We expect these results contribute to improve the quality of biomass estimates across ecosystems, but also to generate methodological consensus on field biomass assessments in shrubs.

ATLANTIC BIRD TRAITS : a data set of bird morphological traits from the Atlantic forests of South America - Rodolpho Credo Rodrigues; Érica Hasui; Julia Camara Assis; João Carlos Castro Pena; Renata L. Muylaert; Vinicius Rodrigues Tonetti; Felipe Martello; André Luis Regolin; Thiago Vernaschi Vieira da Costa; Mauro Pichorim; Eduardo Carrano; Leonardo Esteves Lopes; et al. (Ecology, 2019)
Scientists have long been trying to understand why the Neotropical region holds the highest diversity of birds on Earth. Recently, there has been increased interest in morphological variation between and within species, and in how climate, topography, and anthropogenic pressures may explain and affect phenotypic variation. Because morphological data are not always available for many species at the local or regional scale, we are limited in our understanding of intra‐ and interspecies spatial morphological variation. Here, we present the ATLANTIC BIRD TRAITS , a data set that includes measurements of up to 44 morphological traits in 67,197 bird records from 2,790 populations distributed throughout the Atlantic forests of South America. This data set comprises information, compiled over two centuries (1820–2018), for 711 bird species, which represent 80% of all known bird diversity in the Atlantic Forest. Among the most commonly reported traits are sex ( n = 65,717), age ( n = 63,852), body mass ( n = 58,768), flight molt presence ( n = 44,941), molt presence ( n = 44,847), body molt presence ( n = 44,606), tail length ( n = 43,005), reproductive stage ( n = 42,588), bill length ( n = 37,409), body length ( n = 28,394), right wing length ( n = 21,950), tarsus length ( n = 20,342), and wing length ( n = 18,071). The most frequently recorded species are Chiroxiphia caudata ( n = 1,837), Turdus albicollis ( n = 1,658), Trichothraupis melanops ( n = 1,468), Turdus leucomelas ( n = 1,436), and Basileuterus culicivorus ( n = 1,384). The species recorded in the greatest number of sampling localities are Basileuterus culicivorus ( n = 243), Trichothraupis melanops ( n = 242), Chiroxiphia caudata ( n = 210), Platyrinchus mystaceus ( n = 208), and Turdus rufiventris ( n = 191). ATLANTIC BIRD TRAITS ( ABT ) is the most comprehensive data set on measurements of bird morphological traits found in a biodiversity hotspot; it provides data for basic and applied research at multiple scales, from individual to community, and from the local to the macroecological perspectives. No copyright or proprietary restrictions are associated with the use of this data set. Please cite this data paper when the data are used in publications or teaching and educational activities.

Genetic variant predictors of gene expression provide new insight into risk of colorectal cancer - Stephanie A. Bien; Yu-Ru Su; David V. Conti; Tabitha A. Harrison; Conghui Qu; Xingyi Guo; Yingchang Lu; Demetrius Albanes; Paul L. Auer; Barbara L. Banbury; Sonja I. Berndt; Stéphane Bézieau; et al. (Human Genetics, 2019)

Microparticles and autophagy: a new frontier in the understanding of atherosclerosis in rheumatoid arthritis - C. Barbati; M. Vomero; T. Colasanti; F. Ceccarelli; M. Marcosano; F. Miranda; L. Novelli; A. Pecani; Carlo Perricone; F. R. Spinelli; S. Truglia; F. Conti; et al. (Immunologic Research, 2018)

Species divergence and maintenance of species cohesion of three closely related Primula species in the Qinghai–Tibet Plateau - Guangpeng Ren; Rubén G. Mateo; Antoine Guisan; Elena Conti; Nicolas Salamin (Journal of Biogeography, 2018)
Aim Understanding the relative roles of geography and ecology in driving speciation, population divergence and maintenance of species cohesion is of great interest to molecular ecology. Closely related species that are parapatrically distributed in mountainous areas provide an ideal model to evaluate these key issues, especially when genomic data are analyzed within a spatially and ecologically explicit context. Here, we used three closely related species of Primula that occur in the Himalayas, the Hengduan Mountains and north‐east Qinghai–Tibet Plateau ( QTP ) to examine spatial and ecological effects on interspecific divergence and maintenance of species cohesion. Location Himalayas, the Hengduan Mountains and north‐east QTP. Methods We used genomic data for 770 samples of the three species using double‐digest restriction site‐associated DNA (dd RAD ) sequencing and combined approximate Bayesian computation ( ABC ) modeling, generalized linear mixed modeling ( GLMM ) and niche‐based species distribution modeling ( SDM ). Results The three species are clearly delimited by the RAD seq data. Further ABC modeling indicates that Primula tibetica diverged first followed by a later divergence between Primula nutans and Primula fasciculata . The time frames of the divergences among the three species coincide with the uplifts of the Hengduan Mountains and the northern QTP during the late Miocene and Pliocene followed by a long period of founder events. SDM s indicate that the three species might have survived in different refugia during glaciations and came into secondary contact during the postglacial expansions but with no significant introgression. Finally, GLMM suggests that both the geographical and ecological factors play roles in population differentiation in P. fasciculata and P. tibetica , while for P. nutans , geography is the major driver of genomic variation. The different roles played by geographical and ecological factors in the three species may have affected the maintenance of species cohesion. Main conclusion Our results provide insights of unprecedented details into the start and maintenance of interspecific divergence in the context of changing environments in mountains. Our findings highlight the significance of combining population genomics with environmental data when evaluating the effects of geography and ecology on interspecific divergence and maintenance of closely related species.

An updated checklist of the vascular flora alien to Italy - G. Galasso; F. Conti; L. Peruzzi; N. M. G. Ardenghi; E. Banfi; L. Celesti-Grapow; A. Albano; A. Alessandrini; G. Bacchetta; S. Ballelli; M. Bandini Mazzanti; G. Barberis; et al. (Plant Biosystems, 2018)

An updated checklist of the vascular flora native to Italy - F. Bartolucci; L. Peruzzi; G. Galasso; A. Albano; A. Alessandrini; N. M. G. Ardenghi; G. Astuti; G. Bacchetta; S. Ballelli; E. Banfi; G. Barberis; L. Bernardo; et al. (Plant Biosystems, 2018)

Conserving plant diversity in Europe: outcomes, criticisms and perspectives of the Habitats Directive application in Italy - G. Fenu; G. Bacchetta; V. Giacanelli; D. Gargano; C. Montagnani; S. Orsenigo; D. Cogoni; G. Rossi; F. Conti; A. Santangelo; M. S. Pinna; F. Bartolucci; et al. (Biodiversity and Conservation, 2017)

Altered soil carbon dynamics under different land-use regimes in subtropical seasonally-dry forests of central Argentina - G. Conti; E. Kowaljow; F. Baptist; C. Rumpel; A. Cuchietti; N. Pérez Harguindeguy; S. Díaz (Plant and Soil, 2016)

Fatigue of Metallic Stents: From Clinical Evidence to Computational Analysis - F. Auricchio; A. Constantinescu; M. Conti; G. Scalet (Annals of Biomedical Engineering, 2016)

Erratum to: Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I - A. Artenjak; I. Locatelli; H. Brelih; D. M. Simonič; Z. Ulcova-Gallova; J. Swadzba; J. Musial; T. Iwaniec; L. Stojanovich; F. Conti; G. Valesini; T. Avčin; et al. (Immunologic Research, 2015)

Immunoreactivity and avidity of IgG anti-β2-glycoprotein I antibodies from patients with autoimmune diseases to different peptide clusters of β2-glycoprotein I - A. Artenjak; I. Locatelli; H. Brelih; D. M. Simonič; Z. Ulcova-Gallova; J. Swadzba; J. Musial; T. Iwaniec; L. Stojanovich; F. Conti; G. Valesini; T. Avčin; et al. (Immunologic Research, 2015)

Islands as model systems in ecology and evolution: prospects fifty years after MacArthur‐Wilson - Ben H. Warren; Daniel Simberloff; Robert E. Ricklefs; Robin Aguilée; Fabien L. Condamine; Dominique Gravel; Hélène Morlon; Nicolas Mouquet; James Rosindell; Juliane Casquet; Elena Conti; Josselin Cornuault; et al. (Ecology Letters, 2015)
The study of islands as model systems has played an important role in the development of evolutionary and ecological theory. The 50th anniversary of MacArthur and Wilson's (December 1963) article, ‘An equilibrium theory of insular zoogeography’, was a recent milestone for this theme. Since 1963, island systems have provided new insights into the formation of ecological communities. Here, building on such developments, we highlight prospects for research on islands to improve our understanding of the ecology and evolution of communities in general. Throughout, we emphasise how attributes of islands combine to provide unusual research opportunities, the implications of which stretch far beyond islands. Molecular tools and increasing data acquisition now permit re‐assessment of some fundamental issues that interested MacArthur and Wilson. These include the formation of ecological networks, species abundance distributions, and the contribution of evolution to community assembly. We also extend our prospects to other fields of ecology and evolution – understanding ecosystem functioning, speciation and diversification – frequently employing assets of oceanic islands in inferring the geographic area within which evolution has occurred, and potential barriers to gene flow. Although island‐based theory is continually being enriched, incorporating non‐equilibrium dynamics is identified as a major challenge for the future.

Biodiversity only makes sense in the light of evolution - R Geeta; Lúcia G Lohmann; Susana Magallón; Daniel P Faith; Andrew Hendry; Keith Crandall; Luc de Meester; Cam Webb; Anne-Hélène Prieur-Richard; Makiko Mimura; Elena Conti; Joel Cracraft; et al. (Journal of Biosciences, 2014)

Are Red Lists really useful for plant conservation? The New Red List of the Italian Flora in the perspective of national conservation policies - G. Rossi; C. Montagnani; T. Abeli; D. Gargano; L. Peruzzi; G. Fenu; S. Magrini; M. Gennai; B. Foggi; R.P. Wagensommer; S. Ravera; A. Cogoni; et al. (Plant Biosystems, 2014)

Copper uptake, accumulation and physiological changes in adult grapevines in response to excess copper in soil - Alcione Miotto; Carlos A. Ceretta; Gustavo Brunetto; Fernando T. Nicoloso; Eduardo Girotto; Júlia G. Farias; Tadeu L. Tiecher; Lessandro De Conti; Gustavo Trentin (Plant and Soil, 2014)

Distribution range and ecological niche of Primula marginata Curtis (Primulaceae) - G. Casazza; S. Marsili; L. Granato; E. Conti; V. Noble; A. Selvaggi; L. Minuto (Plant Biosystems, 2013)

Fine resolution distribution modelling of endemics in Majella National Park, Central Italy - H. van Gils; F. Conti; G. Ciaschetti; E. Westinga (Plant Biosystems, 2012)

Mitral Valve Patient-Specific Finite Element Modeling from Cardiac MRI: Application to an Annuloplasty Procedure - Marco Stevanella; Francesco Maffessanti; Carlo A. Conti; Emiliano Votta; Alice Arnoldi; Massimo Lombardi; Oberdan Parodi; Enrico G. Caiani; Alberto Redaelli (Cardiovascular Engineering and Technology, 2011)

Haplotypes of the bovine IgG2 heavy gamma chain in tick-resistant and tick-susceptible breeds of cattle - Wanessa Araújo Carvalho; Patricia Ianella; Frederico G. C. Arnoldi; Alexandre Rodrigues Caetano; Sandra Regina Maruyama; Beatriz Rossetti Ferreira; Luís Henrique Andreucci Conti; Marcia Ramos Monteiro da Silva; José Otavio F. Paula; Antonio Augusto Mendes Maia; Isabel K. Ferreira de Miranda Santos (Immunogenetics, 2011)

A case of primary papillary disseminated adenocarcinoma of canine lung - Maria Beatrice Conti; M. C. Marchesi; G. Angeli; E. Lepri; C. Marinetti; F. Rueca (Veterinary Research Communications, 2010)

Non‐native flora of Italy: Species distribution and threats - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; S. Assini; E. Banfi; E. Barni; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; et al. (Plant Biosystems, 2010)

Measles-induced respiratory distress, air-leak and ARDS - M. Piastra; R. Onesimo; D. Luca; L. Lancella; L. Marzano; G. Rosa; D. Pietrini; P. Valentini; G. Conti (European Journal of Clinical Microbiology & Infectious Diseases, 2010)

Inventory of the non‐native flora of Italy - L. Celesti‐Grapow; A. Alessandrini; P. V. Arrigoni; E. Banfi; L. Bernardo; M. Bovio; G. Brundu; M. R. Cagiotti; I. Camarda; E. Carli; F. Conti; S. Fascetti; et al. (Plant Biosystems, 2009)

Substance P Upregulates LTB4 in Rat Adherent Macrophages from Granuloma Induced by KMnO4 - M. L. Castellani; P. Conti; M. Felaco; J. Vecchiet; C. Ciampoli; G. Cerulli; P. Boscolo; T. C. Theoharides (Neurotoxicity Research, 2009)

Clinical findings and diagnosis in a case of cholangiocellular carcinoma in a horse - M. B. Conti; M. C. Marchesi; F. Zappulla; D. Buttarelli; E. Lepri; F. Passamonti; S. Galletti; G. Rucco; F. Rueca (Veterinary Research Communications, 2008)

Equine adipose-tissue derived mesenchymal stem cells and platelet concentrates: their association in vitro and in vivo - M. Del Bue; S. Riccò; R. Ramoni; V. Conti; G. Gnudi; S. Grolli (Veterinary Research Communications, 2008)

Soil N2O emissions and N2O/(N2O+N2) ratio as affected by different fertilization practices and soil moisture - E. Ciarlo; M. Conti; N. Bartoloni; G. Rubio (Biology and Fertility of Soils, 2008)

Assessment and Behavior of Alphafetoprotein (AFP), Antigen Cancer 15/3 (CA 15/3), Carcinembryonal Antigen (CEA) in Clinical Oncology of the Dog: Preliminary Study - M.C. Marchesi; M.B. Conti; C. Pieramati; V. Mangili; G. Fruganti (Veterinary Research Communications, 2007)

The effect of moisture on nitrous oxide emissions from soil and the N2O/(N2O+N2) ratio under laboratory conditions - E. Ciarlo; M. Conti; N. Bartoloni; G. Rubio (Biology and Fertility of Soils, 2007)

Diet and cooling interactions on physiological responses of grazing dairy cows, milk production and composition - M. R. Gallardo; S. E. Valtorta; P. E. Leva; M. C. Gaggiotti; G. A. Conti; R. F. Gregoret (International Journal of Biometeorology, 2005)

Blood Pressure Measurements in Dogs and Horses Using the Oscillometric Technique: Personal Observations - F. Porciello; F. Birettoni; M.B. Conti; C. Marinetti; M.T. Antognoni; G. Fruganti (Veterinary Research Communications, 2004)

Dynamics of humic fractions and microbial activity under no-tillage or reduced tillage, as compared with native pasture (Pampa Argentina) - Mirta G. Gonzlez; Marta E. Conti; R. Martha Palma; Nilda M. Arrigo (Biology and Fertility of Soils, 2003)

Oxygen supply modulates MCP-1 release in monocytes from young and aged rats: Decrease of MCP-1 transcription and translation is age-related - M. Reale; C. Di Giulio; M. Cacchio; R.C. Barbacane; A. Grilli; G. Bianchi; M. Di Gioacchino; M. Felaco; P. Conti (Molecular and Cellular Biochemistry, 2003)

The CD4 T cell-deficient mouse mutation nackt ( nkt ) involves a deletion in the cathepsin L ( Ctsl ) gene - Fernando Benavides; Ann Venables; Heather Poetschke Klug; Edward Glasscock; Natalia Martin Palenzuela; Claudio J. Conti; Alexander Rudensky; Marcela Gmez; Jean-Louis Gunet; Ellen R. Richie (Immunogenetics, 2001)

Vitamin B6-deficient diet plus 4-deoxypyridoxine (4-DPD) reduces the inflammatory response induced by T. spiralis in diaphragm, masseter and heart muscle tissue of mice - S. Frydas; N. Papaioanou; I. Vlemmas; I. Theodoridis; G. Anogiannakis; D. Vacalis; A. Trakatellis; R.C. Barbacane; M. Reale; P. Conti (Molecular and Cellular Biochemistry, 1999)

IgG, IgG1 and IgM response in Trichinella spiralis-infected mice treated with 4-deoxypirydoxine or fed a Vitamin B6-deficient diet - S. Frydas; M. Reale; D. Vacalis; R.C. Barbacane; F.C. Placido; I. Cataldo; M. Di Gioacchino; E. Karagouni; E. Dotsika; G. Anogiannakis; A. Trakatellis; P. Conti (Molecular and Cellular Biochemistry, 1999)

Expression of lymphocyte subpopulations, cytokine serum levels, and blood and urinary trace elements in asymptomatic atopic men exposed to an urban environment - P. Boscolo; M. Di Gioacchino; E. Sabbioni; F. Benvenuti; P. Conti; M. Reale; P. Bavazzano; G. Giuliano (International Archives of Occupational and Environmental Health, 1999)

Induction of monocyte chemotactic protein-1 (MCP-1) and TNF alpha by Trichinella spiralis in serum of mice in vivo - M. Reale; S. Frydas; R.C. Barbacane; F.C. Placido; I. Cataldo; P. Conti; D. Vacalis; A. Trakatellis; G. Anogianakis; M. Felaco; M. Di Giocchino (Molecular and Cellular Biochemistry, 1998)

Infra-red laser irradiation enhances interleukin-1 receptor antagonist, increases 3H-thymidine incorporation and the release of [3H]arachidonic acid in human monocytes - Marcella Reale; Claudio Orso; Maria Luisa Castellani; Renato Carmine Barbacane; Fernanda Cristina Placido; Ettore Porreca; Concetta Di Febbo; Ivana Cataldo; Demetrio Vacalis; G. Anogianakis; A. Trakatellis; Pio Conti (Molecular and Cellular Biochemistry, 1997)

Protective effects of melatonin in mice infected with encephalitis viruses - D. Ben-Nathan; G. J. M. Maestroni; S. Lustig; A. Conti (Archives of Virology, 1995)

Characterization of rat brain cellular membrane components acting as receptors for vesicular stomatitis virus - C. Conti; P. Mastromarino; M. G. Ciuffarella; N. Orsi (Archives of Virology, 1988)

Inhibitory effect of diamidinophenylindole on the replication of influenza virus in permissive cellular hosts - G. Conti; P. Portincasa (Archives of Virology, 1987)

Different patterns of replication in influenza virus-infected KB cells - G. Conti; P. Valcavi; A. Natali; G. C. Schito (Archives of Virology, 1980)